2020
DOI: 10.1177/2150132720913724
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Problems and Drivers of Health-Related Quality of Life Among Community-Dwelling Older Adults

Abstract: Purpose: The aims of this study were to explore prevalence of health-related problems and identify factors associated with health-related quality of life (HRQOL) among community-dwelling older adults (CDOAs) in rural Thailand. Methods: A total of 384 CDOAs with mean age of 71 years (SD = 7.6) were recruited. The Thai Ministry of Public Health’s comprehensive geriatric assessment (CGA) was used to measure the CDOAs’ health conditions in the primary care unit of community hospitals. HRQOL of the participants was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Participant Recruitment. Recruitment was protracted (June 2018 to February 2019) re ecting high incidences of chronic disease in this population aged > 50y e.g., hypertension (65%), diabetes (23%) 47 , and the low proportion of male recruits. Eighty people answered the advertisement and of these 53 tted the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participant Recruitment. Recruitment was protracted (June 2018 to February 2019) re ecting high incidences of chronic disease in this population aged > 50y e.g., hypertension (65%), diabetes (23%) 47 , and the low proportion of male recruits. Eighty people answered the advertisement and of these 53 tted the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Routine home visits were deemed unnecessarily invasive because: (a) the intervention is commonly consumed as a food or a herbal medication, (b) eBM is a much researched supplement, and (c) most elderly in our catchment area cohabit (94%) and have family caregivers (99%) 47 .…”
Section: Taste Odour and Visual Discrimination Between Interventions:...mentioning
confidence: 99%
“…46 Our study noted that those study participants who had history of a fall in the previous 6 months had a lower HRQOL than participants without a fall, which is similar to the finding in other studies. 17,47 The prevalence of a fall in the 6 months before the date of the interview was 10.3% of our study participants. This is higher than the overall prevalence of a fall among elderly people in the northern region of Thailand (5.5%).…”
Section: Dovepressmentioning
confidence: 86%
“…Previous cross-sectional surveys conducted in northern and northeastern Thailand determined the QOL and associated sociodemographic factors and health-related problems of community-dwelling older adults in the rural setting. 16 , 17 International studies assessing the HRQOL of Thai older adults have been carried out using different measurement tools in different settings. Therefore, we aimed to describe the HRQOL, using representative samples from Northern Thailand, of community-dwelling Thai older adults residing in the urban setting, using the Euro-Qol questionnaire (EQ-5D-5L), and investigate the influence of sociodemographic background, health behaviors and underlying diseases on their HRQOL.…”
Section: Introductionmentioning
confidence: 99%
“…It can range from mild restrictions on the personal freedom to total institutionalization [52]. In a population based cross-sectional study, Taburee et al reported falls to be one of the predictors of health-related quality of life in community-dwelling adults [53]. Recurrent fallers have also been reported to have poor physical performance and a poor quality of life compared to single fallers [54].…”
Section: Impact On Daily Activitiesmentioning
confidence: 99%